Perkawinan Beda Agama Perspektif Hukum Islam dan Surat Edaran Mahkamah Agung Nomor 2 Tahun 2023 - Puput Rama Dona; Burhanuddin; Siti Marlina; Mustiah RH; Eza Tri Yandy (Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research aims to answer three questions: how Islamic and positive law view interfaith marriage, what factors underlie the occurrence of interfaith marriages in Indonesia, and the reasons behind the issuance of Supreme Court Circular (SEMA) Number 2 of 2023. This study employs a normative or doctrinal legal research method, which examines documents and written regulations. The approaches used are the statutory approach and the conceptual approach. The research findings indicate that both Islamic law and positive law in Indonesia share a similar stance, which is to prohibit interfaith marriages as well as marriages with individuals who have no religion. The underlying factors for interfaith marriages in Indonesia include globalization, the modernization of values, family dynamics, socio-economic changes, and religious tolerance. As for the reasons behind the issuance of SEMA Number 2 of 2023, they are driven by the increasing number of interfaith marriage cases in Indonesia, the lack of clarity in existing regulations, alignment with human rights principles, the need to provide legal certainty, reducing the burden on courts, and harmonization with international law